The VERITAS 2023 Iceland Analog Campaign - Nunes, Daniel C.; Smrekar, Suzanne; Hensley, Scott; Adeli, S.; Alemanno, Giulia; Andrews-Hanna, Jeff; Buczkowski, D.L.; Campbell, B.A.; Cascioli, G.; Di Achille, G.; Domac, Akin; Dyar, M. D.; et al. (2024)
Despite near-global scale coverage with Magellan synthetic aperture radar (SAR) imaging of Venus, first-order questions remain about our closest planetary neighbor. This is in part due to (i) remote sensing of the surface restriction to very few wavelengths in the electromagnetic spectrum, and (ii) the low resolution of our best image, topographic, and geophysical data sets. The Venus Emissivity, Radio Science, InSAR, Topography and Spectroscopy (VERITAS) Discovery mission will map the surface with SAR using X-band (4 cm) using the VISAR instrument, and with 6 finely tuned Near-IR bands using the VEM instrument [1]. As a result, it will achieve unprecedented resolution in imagery and topography, as well as detect surface rock types and change over time. To support interpretation of X-band and NIR data, test data processing algorithms, and comparison with S- band SAR from other missions (Magellan, EnVision), the VERITAS Science Team conducted a field analog campaign over two weeks in August 2023 in collaboration with the German Aerospace Center (DLR), which involved both an airborne radar mapping effort and an in-situ surface characterization task. The latter provides ground truth for parameters that affect radar backscatter (topography, roughness, dielectric permittivity) and NIR emissivity.